Impact of Dried Stems on the Chemical Profile of Passito Wines: A Case Study of Four Veneto Varieties - Giovanni Luzzini; Loris Colognato; Leonardo Vanzo; Jessica Anahi Samaniego Solis; Naíssa Prévide Bernardo; Rosario Pascale; Beatrice Perina; Giacomo Cristanelli; Maurizio Ugliano; Davide Slaghenaufi (Fermentation)
In winemaking, the use of stems during fermentation is rarely employed due to some undesirable side effects. While the effect of fresh stems on wine is extensively studied, to date limited information is available about the effect of dried stems. This study aimed to investigate the impact of dried stems on the chemical and sensory profile of passito wines. Four withered grape varieties were selected for winemaking: three red and one white from the Verona area. Grapes were fermented with and without withered stems. A major impact on enological parameters, in particular pH and total polyphenols, was observed. In terms of volatile compounds, no release of C6 alcohols—compounds with undesirable herbaceous odors—was detected. Varietal-dependent release of 3-isobutyl-2-methoxypyrazine (IBMP) was also observed; however in most cases, the content was below the odor threshold. Furthermore, dried stems significantly decreased methanethiol content, likely due to adsorption phenomena. Minor differences were observed in acetate esters, terpenes, and norisoprenoids, though these were not consistent across all wine types. From a sensory point of view, a significant variety-dependent effect was observed, mostly due to IBMP, ethyl acetate, and β-damascenone.